Accumulating Evidence Supports a Taste Component for Free Fatty Acids in Humans - Mattes, Richard D. (2011)
The requisite criteria for what constitutes a taste primary have not been established. Recent advances in understanding of the mechanisms and functions of taste have prompted suggestions for an expanded list of unique taste sensations, including fat, or more specifically, free fatty acids (FFA). A set of criteria are proposed here and the data related to FFA are reviewed on each point. It is concluded that the data are moderate to strong that there are: A) adaptive advantages to FFA detection in the oral cavity; B) adequate concentrations of FFA to serve as taste stimuli; C) multiple complimentary putative FFA receptors on taste cells; D) signals generated by FFA that are conveyed by gustatory nerves; E) sensations generated by FFA that can be detected and scaled by psychophysical methods in humans when non-gustatory cues are masked; and F) physiological responses to oral fat/FFA exposure. On no point is there strong evidence challenging these observations. The reviewed findings are suggestive, albeit not definitive, that there is a taste component for FFA.